The Impact of Gender, Parents’ Education Level, and Socio-Economic Status on Turkish Students’ Mathematics Performance - Rusli Rusli (SEAMEO Regional Centre for QITEP in Mathematics, 2017)
This paper describes secondary data analyses that investigate the impact of gender, parents’ education level, and socio-economic status upon Turkish students’ mathematics achievement in the Program for International Student Assessment (PISA) 2009. The analyses were done quantitatively using t-tests, one-way ANOVA, correlation and linear regression. The findings revealed that gender differences and Turkish students’ mathematics performance are statistically significant but practically not significant. Parents’ education level had an impact on Turkish students’ mathematics achievements. The index of Economic, Social and Cultural Status (ESCS) had a positive effect on mathematics achievements and ESCS was a significant predictor of Turkish students’ mathematics performance. The findings seem to suggest that at the school level, the school environment is expected to build students’ motivation in learning, and the teachers in the classroom setting are expected to provide extra hours and learning consultation services for students who need it. At the student level, students were expected to have high motivation in learning and are suggested to not rely on learning facilities provided by their parents. However, further research is required prior to making any recommendations on school policy, teaching, and learning practice in the classroom setting.